Estudio de la interacción suelo - atmósfera en el suelo blando de la ciudad de Bogotá (2019)
In this grade work were studied the changes produced in the volumetric water content of the soil of the Bogotá savannah for four depths as a function of time, these changes were generated by the interaction between the atmosphere and the soil due to the change of atmospheric variables. Six water flow models were carried out that allowed relate the atmospheric variability and predict the humidity changes and potential of soil suction through the results of a numerical model. The results of the numerical modeling were compared with the humidity measured with electronic sensors that are part of a project developed at the Colombian School of Engineering. The numerical results obtained were compared with the experimental data through the calculation of statistical errors resulting in a good estimation of the results measured with the simulated ones.